Responsibilities of school: the review of research student policies - Zainal Abiddin, Norhasni (Medwell Journals, 2008)
In every university, there is code of practice or policy for graduate research student which contained in the student handbook. Every student will be given this handbook during their registration at the university. What actually contained in research student policy? In general, research student policy contains information about responsibilities of student, supervisor, school and recommended practices which supposed to be done by student, supervisor and school. Part of this policy was designed to protect the student's interest and welfare. Hence there were 40 graduate research student policies have been studied from 40 universities in the United Kingdom. This article will explore in detail about research student policies which focusing on responsibilities of school.